Chaotic quantization based JPEG for effective compression of whole slide images - Artuğer, Fırat; Özkaynak, Fatih (Springer Science and Business Media Deutschland GmbH, 2023)
In today’s digital world, effectively transferring data from one point to another is an important problem. For this reason, the development of various new compression algorithms and making existing solutions more effective are examined in detail by researchers. In this study, a new method is proposed to improve the performance of JPEG algorithm. The proposed method includes an approach based on chaotic systems. Chaotic systems contain a strong entropy source. This powerful source of entropy has strong practical applications in obtaining statistically robust random values. In this study, a method is proposed to obtain quantization tables effectively by taking advantage of this potential of chaotic systems. The obtained results showed that the compression performance can be increased at the same quality factors. The proposed approach has been tested on the whole slide image (WSI) dataset. Looking at the analysis results, an average of 2.43% higher accuracy was achieved compared to the JPEG algorithm. It is thought that these results can provide an advantage especially in transferring high-dimensional images such as the DICOM standard, where the JPEG algorithm is used in practical applications. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Chaos; Compression; Digital pathology; JPEG; Whole slide image